Comparison of the efficacy and safety of third-line treatments for advanced gastric cancer: A systematic review and network meta-analysis - Zhang, Chan; Xiang, Yaoxian; Wang, Jing; Yan, Dong (Frontiers in Oncology, 2023)
Background: Many options for third-line treatment of advanced gastric cancer (GC) or gastroesophageal junction carcinoma (GEJC) have been developed. Therapies including immunotherapy (nivolumab), chemotherapy (irinotecan, FTD/TPI), targeted therapy (apatinib), and antibody drug conjugates (ADC) have shown to increase the survival rates in patients, but few studies have compared the relative efficacy of these treatments. Here, we compared the efficacies of these regimens using network meta-analysis (NMA) to provide guides in selecting the best regimen and formulating a precise individualized treatment plan. Methods：The published RCTs of phase II/III in PubMed, the Cochrane Central Register of Controlled Trials, and Embase were searched. The median overall survival (mOS) was the primary outcome of NMA, and the other outcomes were median progression-free survival (mPFS), disease control rate (DCR), and incidence of grade 3 or above adverse events (≥3AEs). Results: Five phase II/III RCTs involving 1674 patients and 7 treatment regimens were analyzed. It showed that for the overall population, DS-8201 prolonged the OS of patients significantly comparing with chemotherapy (HR: 0.59; 95% CI: 0.39-0.89). DS-8201 (HR: 0.27; 95% CI: 0.17-0.42) and chemotherapy (HR: 0.57; 95% CI: 0.47-0.7) improved the PFS significantly over nivolumab. For DCR, apatinib (RR: 3.04; 95% CI: 1.65-5.95) and DS-8201 (RR: 2.67; 95% CI: 1.51-4.83) were more effective than nivolumab. DS-8201 achieved greater OS benefits compared to chemotherapy (HR: 0.59; 95% CI: 0.39-0.88) for patients who were HER2-positive. We ranked the Bayesian surface under the cumulative ranking curve according to OS benefit, and showed that ADC ranked first for the general patient population and for patients with a HER2-positive diagnosis, intestinal histopathology, previous gastrectomy history, gastric origination cancer, over 65 years old and ECOG PS=0/1, followed by nivolumab and apatinib. For patients with GEJC, nivolumab ranked first. Conclusions: Nivolumab, apatinib, chemotherapy, and ADC all improved the OS of GC/GEJC patients significantly. ADC may be the best option for the overall population of GC, as well as for patients with HER2-overexpression, intestinal histopathology, previous gastrectomy history, gastric origination cancer, over 65 years old and ECOG PS=0/1, followed by nivolumab and apatinib. Nivolumab may be the first treatment option for GEJC patients.